Comparison between Kinesio Taping & Traditional Physical Therapy Rehabilitation for treatment of Non-Specific Back Pain - M. Shahid Akhtar, Sania Maqbool, Junaid Sadiq, Afeera Tariq, M. U. Ashraf, Zainab Tehreem6, Bayyaniha Zaheer, U. Jamil, M. Hayat (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To see the comparative effectiveness of Conventional physiotherapy with kinesio Taping and Conventional physiotherapy alone to reduce pain and increase Range of Motion (ROM) in patients with non-specific low back pain. Methodology: The study design was Randomized controlled trail. Non-probability Temporal method sampling technique was used. Sample size was 36. The data was collected from Department of Physiotherapy Mayo Hospital Lahore. Written informed contest was taken from each patients taking part in this prior to performing any examination. Patients with non-specific low back pain were divided randomly into two groups. In ‘group A’ Conventional physiotherapy with Kinesio Taping was applied while in ‘group B’ only conventional physiotherapy was applied. The patients were divided into two groups using a computer-generated list. Both groups will receive conventional therapy, which will remain same throughout the study. The conventional therapy will include back isometrics and hot pack for 15 minutes. Group A will receive conventional therapy and Kinesio Taping while group B will receive only conventional therapy. Treatment frequency will be thrice a week. The duration of treatment was be 2 weeks in both groups. Each patient’s informed consent was obtained before Performa was filled out. The Roland Morris Disability Questionnaire and the Visual Analogue Scale (VAS) were both utilized for scoring. Results: Kinesio Taping with Traditional Physical Therapy technique is more effective in improving ROM and reducing disability as compared to only Traditional Physical Therapy technique. Patients in group A showed marked improvement as compared to group B. Conclusion: it was concluded that conventional physiotherapy with Kinesio Taping is more effective than Conventional physiotherapy alone for the treatment of low back pain. Conventional physiotherapy with Kinesio Taping not only decrease pain but also improves function and flexibility of spine. Key words: Non-specific low back pain, Kinesio-taping, Traditional physical therapy, RCT, Rehabilitation